Behaviour of axially compressed CTHST stub columns with inner spiral stirrup. (November 2022) - Yang, You-Fu; Zhang, Yu-Qin; Fu, Feng
Abstract: In this paper, a new type of concrete-filled thin-walled high-strength steel tube (CTHST) columns with inner spiral stirrup is proposed. This new type of columns provides dual constraints to the concrete core by both outer steel tube and inner spiral stirrup. To explore the structural performance of this new type of composite members, a pilot study into stub columns under axial compression was carried out. A total of 16 axially compressed specimens, 8 in circular section and 8 in square section, were tested with the various volumetric stirrup ratio ( ρ, from 0 to 2.4 %) and yield strength of steel tube ( f y t, 571.2 MPa and 648.9 MPa). The experimental results show that, the inner spiral stirrup has little impact on the overall failure pattern of each component of the specimens, but controls the horizontal angle of the failure plane, and the capacity, composite elastic modulus and ductility coefficient of the specimens increase as ρ and f y t increase. In addition, a nonlinear finite element (FE) model was established, and the representative mechanism of axially compressed CTHST stub columns with inner spiral stirrup under different ρ was further studied by the verified FE model. Finally, a calculation method to predict the capacity of the new composite members was developed, which considers the strength improvement of stirrup confined concrete. This method provided an accurate prediction of the capacity of axially compressed CTHST stub columns with inner spiral stirrup.